Optical solitons to the resonance nonlinear Schrodinger equation by Sine-Gordon equation method - İnç, Mustafa; Aliyu, Aliyu Isa; Yusuf, Abdullahi; Baleanu, Dumitru (Academic Press Ltd- Elsevier Science Ltd, 2018)
In this paper, we examined the optical solitons to the resonant nonlinear Schrodinger equation (R-NLSE) which describes the propagation of solitons through optical fibers. Three types of nonlinear media fibers are studied. They are; quadratic-cubic law, Kerr law and parabolic law. Dark, bright, dark-bright or combined optical and singular soliton solutions are derived using the sine-Gordon equation method (SGEM). The constraint conditions that naturally fall out of the solution structure which guarantee the existence of these solitons are also reported. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Sine-Gordon equation method; Optical solitons; Resonant nonlinear Schrodinger equation